Data comparison on fumes local exhaust ventilation: Examination and testing compliance to USECHH regulation 2000 - Hasan, Nor Halim; Said, Md Radzai; Leman, Abdul Mutalib; D.Pagukuman, B. Norerama; Othman, Jaafar (2012)
The paper focused on the examination and testing of local exhaust ventilation (LEV) systems at one of Electrical Company to check the transport velocity whether it meet the recommended American Governmental Industrial Hygienist (ACGIH) Standard. The industrial hygiene approaches, AREC (Anticipating, Recognize, Evaluate and Control) were adopted in this study. This is to ensure that the LEV system installed has the optimum efficiency to extract out the contaminants from the workstation. Objective of this study is to make comparison with previous and current monitoring data. The efficiency and the other parameter measured will be the main source to analyze for the particular applications. The differential of data was discussed and several recommendations are proposed to make sure the LEV system performance is excellent.